Preparation, Characterization and Antibacterial Activity of Pomegranate Peel Extract and Chitosan-Silver Nanoparticles Using Electrochemical Method. - Sarhan, Afaf; Hamid, M. I. Abdel; Omar, Sabrien A.; Hanie, R. (JOURNAL OF ADVANCES IN PHYSICS, 2020)
The present work involves the development of chitosan-pomegranate peel extract and silver nanoparticles (Cs-PPE-AgNPs) using electrochemical process followed by UV irradiation reduction. Formation of silver nanoparticles characterize by UV–vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), differential thermal analysis (DTA), SEM, Swelling and thermal gravimetric analysis (TGA). The obtain nanoparticles average size was 34.6 nm. UV Spectroscopy show new peak at 405nm indicate the formation of AgNPs particles. Cs-PPE and Cs-PPE-AgNPs also demon started a relativity high antibacterial against Escherichia coli and Staphylococcus aureus bacteria.